Preparation method and application of Fe-N-C aerogel

The Fe-NC aerogel synthesis addresses low catalytic activity and separation issues, enabling efficient degradation of PPCPs and broadening applications by providing a recyclable and environmentally friendly catalyst form.

CN119236990APending Publication Date: 2025-01-03SHAOXING MUNICIPAL DESIGN INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411171603.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing Fe-NC catalysts face challenges such as low catalytic activity, single active species production, environmental stability issues, and difficulty in separation and recovery, posing risks to aquatic ecosystems and limiting their application in water treatment.

Method used

A method to prepare Fe-NC aerogel by synthesizing iron-doped melamine formaldehyde resin, followed by calcination in a nitrogen atmosphere, resulting in a form that can be shaped and recycled, with enhanced catalytic activity and dual confinement effects.

Benefits of technology

The Fe-NC aerogel effectively activates persulfate to degrade toxic organic pollutants, including PPCPs, with high removal rates and recyclability, reducing environmental impact and broadening application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236990A_ABST
    Figure CN119236990A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of Fe-N-C aerogel, and belongs to the technical field of nitrogen-containing compound catalysts. Adding melamine and formaldehyde into deionized water to form a mixed turbid solution, and heating and stirring the mixed turbid solution until the mixed turbid solution is clear; cooling to room temperature, adjusting the pH to be acidic, adding anhydrous ferrous chloride, stirring to react until solids are completely dissolved, and heating and aging until the solution is completely gelled; freeze-drying the gel, calcining in a tube furnace in a nitrogen atmosphere, naturally cooling, taking out, repeatedly soaking with hydrochloric acid, washing, and carrying out suction filtration to obtain the Fe-N-C aerogel with the double confinement effect. The Fe-N-C aerogel is high in catalytic capacity, rich in active sites and good in cyclic utilization performance, the defect that a powder catalyst is prone to loss is overcome, the Fe-N-C aerogel can be converted into various shapes by changing a casting container, and the application scene of Fe-N-C is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method and application of Fe-NC aerogel, and belongs to the technical field of nitrogen-containing compound catalysts. Background Art

[0002] With the continuous growth of population, the demand for water in agriculture and industry has increased. Water pollution and water ecological damage have become one of the key factors restricting the high-quality and sustainable development of society. The relevant goal recommendations for national economic and social development clearly put forward the concept of "paying attention to the control of new pollutants". In order to fight the tough battle of pollution prevention and control and promote the high-level protection of the ecological environment, the control of new pollutants cannot be absent. The relevant new pollutant control action plan clarifies the particularity of new pollutants that are different from conventional pollutants. Such new pollutants are pollutants that have been recently discovered or concerned, pose risks to the ecological environment or human health, have not yet been included in the management, or the existing management measures are not sufficient to effectively prevent and control their risks. Pharmaceuticals and Personal Care Products (PPCPs) are the new pollutants that are most exposed in daily life. PPCPs are widely used in human medicine, cosmetics, health products, aquatic products and animal husbandry and other industries. About 3 billion tons of PPCPs are consumed every year worldwide. The large-scale use of PPCPs leads to their inevitable and continuous entry into the water environment. Various PPCPs can be detected in multiple surface waters and groundwaters, with concentrations reaching ng / L-μg / L levels. This poses potential risks to human health and the ecological environment. PPCPs pollution has attracted widespread attention from the society.

[0003] Advanced Oxidation Processes (AOPs) are a new type of chemical decontamination technology that activates oxidants containing peroxide bonds through energy radiation, transition metals, carbonaceous materials, etc., causing them to quickly produce strong oxidizing species, thereby achieving efficient degradation and inactivation of organic pollutants and pathogenic microorganisms in water. At present, advanced oxidation processes based on hydrogen peroxide, ozone, and persulfate have engineering examples in the fields of sewage treatment, drinking water treatment, soil remediation, etc., but their further promotion is restricted by defects such as low catalytic efficiency, long treatment cycle, and obvious secondary pollution. The exploration and optimization of heterogeneous advanced oxidation processes can effectively overcome the above defects and help expand the application scope of advanced oxidation processes. Fe-NC is a polymorphic active ligand unit (Fe-N 6 、Fe-N 4 、Fe-N 2) is a new type of catalyst that can efficiently activate a variety of oxidants to produce active species. Compared with traditional zero-valent iron or iron oxides, Fe-NC is extremely stable and can withstand the corrosion of acidic oxidants, avoiding secondary pollution caused by the dissolution of metal ions into the water to be treated. However, the catalytic activity of Fe-NC is lower than that of zero-valent iron or iron oxides, and the active species produced by the activated oxidant are single, with strong selectivity for organic pollutants, and can only be used for targeted removal of certain types of special organic matter. In addition, unlike other iron-based catalysts, Fe-NC is not magnetic, and Fe-NC in powder form is difficult to separate and recover when used for water treatment. Fe-NC nanoparticles leaked into the environment are highly stable and also pose a potential threat to aquatic plants and animals. Therefore, the enhancement of the catalytic activity of Fe-NC catalysts and the optimization and improvement of environmental friendliness are still the pain points and needs of the industry. Summary of the invention

[0004] In view of this, the present application provides a method for preparing a Fe-NC aerogel, wherein the Fe-NC aerogel has strong catalytic ability, abundant active sites, and good recyclability.

[0005] Specifically, the present application is implemented through the following scheme: A method for preparing Fe-NC aerogel, the steps are as follows: Step 1: adding melamine and formaldehyde into deionized water to form a mixed turbid liquid, and heating and stirring the mixed turbid liquid until it becomes clear; Step 2: Cool to room temperature, adjust pH to acidic, add anhydrous ferrous chloride, stir to react until the solid is completely dissolved, and heat and age until the solution is completely gelled; Step 3: After the gel is freeze-dried, it is placed in a tubular furnace and calcined in a nitrogen atmosphere, cooled naturally, taken out, repeatedly soaked in hydrochloric acid, washed, filtered, and zero-valent iron or iron oxide is etched away to obtain Fe-NC aerogel with a dual confinement effect.

[0006] The above scheme first synthesizes iron-doped melamine formaldehyde resin, and then calcines the iron-doped melamine formaldehyde resin at high temperature in a nitrogen atmosphere to obtain Fe-NC aerogel. Its aerogel form overcomes the disadvantage of easy loss of powder catalyst, and can be transformed into various shapes by changing the casting container, broadening the application scenarios of Fe-NC.

[0007] Further, preferably: In step one, The molar ratio of melamine to formaldehyde is 1:3-4, and preferably 1:3.7.

[0008] The solid concentration in the mixed turbid liquid is 4-6 wt %, and preferably 5 wt %.

[0009] The heating and stirring temperature is 60-80°C, and preferably 70°C.

[0010] In step 2, The pH is adjusted by using any one of hydrochloric acid, nitric acid and sulfuric acid, and hydrochloric acid is preferred.

[0011] The pH is adjusted to 1.6-1.8.

[0012] The amount of anhydrous ferrous chloride relative to formaldehyde is 0.025-0.1 g / mL, and preferably 0.05 g / mL.

[0013] The aging temperature is 80-105°C, and preferably 95°C.

[0014] In step 3, the calcination temperature is 780-920°C, and the calcination time is 3-8 hours. More preferably, the calcination temperature is 850°C, and the calcination time is 3 hours. The temperature is raised from room temperature to the calcination temperature at a rate of 3-6°C / min.

[0015] By immersing the Fe-NC aerogel prepared by the above method as a catalyst in a solution containing persulfate and PPCPs, the persulfate can be activated to achieve efficient removal of various toxic and harmful difficult-to-degrade organic micropollutants PPCPs in water, including medicines and personal care products.

[0016] During the above removal process, the solution temperature is controlled at 15~45 ℃.

[0017] The PPCPs include drugs and personal care products, specifically, various antibiotics, synthetic musks, analgesics, antihypertensive drugs, contraceptives, hypnotics, diet pills, hair sprays, hair dyes and fungicides, etc. Specifically, PPCPs include any one or more of nitrobenzene, benzoic acid, p-hydroxybenzoic acid, phenol, aniline and bisphenol A.

[0018] In the application of the above-mentioned aerogel, the Fe-NC aerogel is immersed in a solution containing persulfate and PPCPs to achieve efficient removal of PPCPs in water. The Fe-NC aerogel proposed in the present invention has strong catalytic ability, rich active sites, good recyclability, and can activate persulfate to oxidatively remove various toxic and harmful organic micropollutants that are difficult to degrade, including drugs and personal care products. In addition, the aerogel form overcomes the disadvantage that the powder catalyst is easy to lose and can be transformed into various shapes by changing the casting container, broadening the application scenarios of Fe-NC. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0020] Figure 1 The scanning electron microscope and transmission electron microscope energy spectrum scanning images of Fe-NC aerogel; Figure 2 is the X-ray diffraction pattern of Fe-NC aerogel; Figure 3 Comparison of the effects of different systems activated with potassium persulfate on the degradation of different bisphenol A; Figure 4 Comparison of the effects of catalytic systems on degrading different PPCPs. DETAILED DESCRIPTION

[0021] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0022] Example 1

[0023] In this example, Fe-NC aerogel is prepared in the following process: 1.26 g of melamine and 4 mL of formaldehyde were mixed in 16 mL of deionized water and stirred in a 70 °C water bath for 20 min until the solution was clear. After the solution was cooled to room temperature, sulfuric acid was used to adjust the pH of the solution to 1.6. Then 0.1 g, 0.2 g or 0.4 g of anhydrous ferrous chloride were added respectively and stirred for 10 min until the solid was completely dissolved. The clarified solution was transferred to a 95 °C oil bath and aged for 24 h. The obtained hydrogel was then placed in a freeze drying oven and dried for 24 h. The obtained aerogel was then placed in a tubular furnace and calcined in a nitrogen atmosphere for 3 h. The calcination temperature was 850 °C and the heating rate was 6 °C / min. After the tubular furnace was naturally cooled, the aerogel was taken out, repeatedly soaked in hydrochloric acid, washed and filtered to obtain Fe-NC aerogel.

[0024] Among them, the aerogels obtained by adding 0.1g, 0.2g, and 0.4g of anhydrous ferrous chloride were recorded as 0.1Fe-SACAs, 0.2Fe-SACAs, and 0.4Fe-SACAs, respectively, and the aerogel corresponding to the blank group (without adding anhydrous ferrous chloride) was recorded as CAs.

[0025] The performance of the obtained Fe-NC aerogel was tested, and the results are as follows Figure 1 and Figure 2 shown.

[0026] Figure 1 (a) is the scanning electron micrograph of Fe-NC aerogel. Figure 1 (b) and (c) are transmission electron microscope energy spectrum scanning images of Fe-NC aerogel. It can be seen that Fe-NC aerogel has a rich pore structure, mainly composed of uniform C elements, and Fe and N elements are uniformly dispersed in it.

[0027] Figure 2 This is the X-ray diffraction diagram of Fe-NC aerogel (XFe-SACAs, X represents the amount of anhydrous ferrous chloride). It can be seen that Fe-NC aerogel does not contain impurities such as zero-valent iron, iron element, and iron oxide. It is pure Fe-NC with typical single-atom iron characteristics, which is consistent with Comparative Example 1 (CN116273110A). However, this application abandons the traditional powder form and synthesizes Fe-NC in the form of aerogel, overcoming the disadvantage of easy loss of powder catalysts, and can be transformed into various shapes by changing the casting container, broadening the application scenarios of Fe-NC; at the same time, the aerogel structure not only maintains the Fe-NC structural confinement, but also uses the nanopore structure of the aerogel to produce new spatial confinement, and the double confinement effect further enhances the catalytic activity of Fe-NC.

[0028] The Fe-NC aerogel prepared by the above method is used to activate persulfate to degrade organic pollutants in water.

[0029] Application Examples

[0030] The method of using Fe-NC aerogel to activate persulfate to degrade bisphenol A (BPA) in water is as follows: A bisphenol A aqueous solution was prepared as the treatment solution, with a volume of 100 mL and an initial bisphenol A concentration of 10 mg / L. 1 mmol / L potassium persulfate and 0.1 g / L Fe-NC aerogel were added to the bisphenol A solution, and a magnetic stirrer was started to react at room temperature for 30 min. The results are as follows: Figure 3As shown: the blank group CAs had almost no activation effect, while the removal rates of bisphenol A by 0.1Fe-SACAs, 0.2Fe-SACAs, and 0.4Fe-SACAs were all over 99%, especially the treatment effect of 0.2Fe-SACAs, which was significantly better than other control treatment groups.

[0031] Fe-NC aerogel activated persulfate to degrade various organic pollutants in water, including nitrobenzene (NB), benzoic acid (BA), p-hydroxybenzoic acid (HBA), phenol (Ph) and aniline (An). Taking 0.2Fe-SACAs as an example, the removal effects of various organic pollutants are as follows: Prepare an aqueous solution containing organic pollutants as the solution to be treated, with a volume of 100 mL and an organic pollutant concentration of 10 mg / L. Add 1 mmol / L potassium persulfate and 0.1 g / L 0.2Fe-SACAs to the solution to be treated, start the magnetic stirrer and react for 30 min at room temperature. Figure 4 , the removal rates of HBA, Ph, and An were all over 80%, and the removal rates of NB and BA were close to 50%, indicating that the Fe-NC aerogel prepared in this application had a good removal effect on most organic pollutants when degrading different PPCPs.

[0032] Comparative Example

[0033] CN116273110A is used as comparative example 1. Compared with comparative example 1, the advantages and differences of the present application are as follows: First, the Fe-NC proposed in this application is in the form of aerogel, and its shape can be changed by changing the casting container. The product is easier to recycle than powder materials and does not cause secondary pollution to water bodies.

[0034] Secondly, the Fe-NC aerogel proposed in the present application can activate persulfate to degrade organic pollutants without light, thereby reducing energy use and being more environmentally friendly.

[0035] Again, the Fe-NC aerogel proposed in the present application has the ability to activate persulfate to degrade stubborn organic pollutants (such as NB and BA), while the comparative examples only show some embodiments using easily degradable organic matter as objects.

[0036] The Fe-NC aerogel proposed in the present invention has strong catalytic ability, rich active sites, good recyclability, and can activate persulfate to oxidize and remove various toxic and harmful organic micropollutants that are difficult to degrade, including drugs and personal care products. In addition, the aerogel form overcomes the disadvantage that the powder catalyst is easy to lose and can be transformed into various shapes by changing the casting container, broadening the application scenarios of Fe-NC.

[0037] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.

Claims

1. A method for preparing Fe-NC aerogel, characterized in that: Here are the steps: Step 1: adding melamine and formaldehyde into deionized water to form a mixed turbid liquid, and heating and stirring the mixed turbid liquid until it becomes clear; Step 2: Cool to room temperature, adjust pH to acidic, add anhydrous ferrous chloride, stir to react until the solid is completely dissolved, and heat and age until the solution is completely gelled; Step 3: After the gel is freeze-dried, it is placed in a tubular furnace and calcined in a nitrogen atmosphere, cooled naturally, taken out, repeatedly soaked in hydrochloric acid, washed, and filtered to obtain a Fe-NC aerogel with a double confinement effect, wherein the double confinement effect includes the structural trapping of Fe-NC and the spatial confinement generated by its aerogel nanopore structure.

2. The method for preparing Fe-NC aerogel according to claim 1, characterized in that: In step 1, the molar ratio of melamine to formaldehyde is 1:3-4.

3. The method for preparing Fe-NC aerogel according to claim 1, characterized in that: In step 1, the solid concentration in the mixed turbid liquid is 4-6 wt%.

4. The method for preparing a Fe-NC aerogel according to claim 1, characterized in that: In step 1, the temperature of the heating and stirring is 60-80°C.

5. The method for preparing Fe-NC aerogel according to claim 1, characterized in that: In step 2, the pH is adjusted to 1.6-1.8 using any one of hydrochloric acid, nitric acid and sulfuric acid.

6. The method for preparing Fe-NC aerogel according to claim 1, characterized in that: In step 2, the aging temperature is 80-105°C.

7. The method for preparing Fe-NC aerogel according to claim 1, characterized in that: In step 2, the amount of anhydrous ferrous chloride relative to formaldehyde is 0.025-0.1 g / mL.

8. The method for preparing Fe-NC aerogel according to claim 1, characterized in that: In step three, the calcination temperature is 780~920°C, and the calcination time is 3~8 h.

9. An application of the Fe-NC aerogel prepared by the method of claim 1, characterized in that: Fe-NC aerogel was immersed in a solution containing persulfate and PPCPs as a catalyst, and the solution temperature was controlled at 15-45 °C to activate persulfate and remove PPCPs.

10. The use of the Fe-NC aerogel according to claim 9, characterized in that: The PPCPs are one or more of nitrobenzene, benzoic acid, p-hydroxybenzoic acid, phenol, aniline and bisphenol A.